2012
DOI: 10.1186/1475-2840-11-73
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac fibrosis and dysfunction in experimental diabetic cardiomyopathy are ameliorated by alpha-lipoic acid

Abstract: BackgroundAlpha-lipoic acid (ALA), a naturally occurring compound, exerts powerful protective effects in various cardiovascular disease models. However, its role in protecting against diabetic cardiomyopathy (DCM) has not been elucidated. In this study, we have investigated the effects of ALA on cardiac dysfunction, mitochondrial oxidative stress (MOS), extracellular matrix (ECM) remodeling and interrelated signaling pathways in a diabetic rat model.MethodsDiabetes was induced in rats by I.V. injection of stre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
97
0
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 154 publications
(109 citation statements)
references
References 39 publications
10
97
0
2
Order By: Relevance
“…Studies with natural antioxidants such as vitamin E, vitamin C, and a-lipoic acid have yielded promising results in animal models of diabetes, particularly when STZ is used to induce hyperglycemia (7,57). However, when investigated in humans, these antioxidants either alone or in combination have not shown consistent beneficial effects on serum metabolic parameters or the incidence of cardiovascular disease (65,108).…”
Section: Antioxidant Therapiesmentioning
confidence: 99%
“…Studies with natural antioxidants such as vitamin E, vitamin C, and a-lipoic acid have yielded promising results in animal models of diabetes, particularly when STZ is used to induce hyperglycemia (7,57). However, when investigated in humans, these antioxidants either alone or in combination have not shown consistent beneficial effects on serum metabolic parameters or the incidence of cardiovascular disease (65,108).…”
Section: Antioxidant Therapiesmentioning
confidence: 99%
“…Autophagy is involved in the intracellular degradation of type I collagen for the prevention of excess ECM deposition (3,72,82). There is also evidence that impaired autophagy promotes differentiation of fibroblasts to myofibroblasts, the profibrotic phenotype of fibroblasts (2,96). Although studies have reported increased activation of cardiac fibroblasts and fibrosis in diabetic hearts, no studies have examined whether autophagy plays a role in this response.…”
Section: Autophagy In Cell Types Beyond the Cardiomyocytementioning
confidence: 99%
“…Alpha lipoic acid (ALA), also named as thiotic acid, is a natural cofactor that is synthesized inside the plant and animal mitochondria (Thaakur and Himabindhu, 2009). ALA has recently used as a protective agent for many pathological alterations that are due to oxidative stress (Li et al, 2012 andWang et al, 2013). The antioxidant activity of ALA may discussed by its ability to scavenge free radicals in both lipophilic and hydrophilic environments, and to restore endogenous antioxidants, chelate transition metals, decrease lipid oxidation, prevent protein glycation and repair oxidatively damaged biomolecules (Palaniyappan and Alphonse, 2011).…”
Section: Introductionmentioning
confidence: 99%